Qualitative evaluation of the Saleema campaign to eliminate female genital mutilation and cutting in Sudan - Andrea C. Johnson; W. Douglas Evans; Nicole Barrett; Howida Badri; Tamador Abdalla; Cody Donahue (BMC, 2018)
Abstract Background Female genital mutilation and cutting (FGM/C, herein FGM) is a widespread and harmful practice. The Government developed a national campaign in Sudan, called Saleema, to change social norms discouraging FGM. Saleema translates to being "whole", healthy in body and mind, unharmed, intact, pristine, and untouched, in a God-given condition. An interim evaluation was conducted using focus groups among Sudanese adults. The primary aim was to explore perceptions of the Saleema poster exemplars and to assess if the desired themes were being communicated. Secondary aims were to understand more about participants' information sources, values, and suggestions for the campaign broadly. Methods The Saleema campaign evaluation included four focus groups from each of the 18 states in Sudan (72 total). Participants were presented with three poster stimuli from the Saleema campaign and asked about the content and their reactions. Themes were coded inductively by concepts that arose through content in the transcripts. Codes were also reviewed in conjunction with themes from the broader Saleema evaluation framework. Results Participants reported the most common source of information or admiration was from local leaders who are responsive to a community, media-based outlets, and discussions among community members. Participants held high value for education, community solidarity, and/or religious devotion. Participants had positive opinions of Saleema and responded positively to the branding elements in the posters and the campaign as a whole. The most common suggestion was continued awareness. Advocacy, training, and posters were suggested to highlight the harms of FGM through leaders or in community settings. Individuals suggested that these activities target older women and individuals in rural villages. There was also a burgeoning theme of targeting youth for support of the campaign. Discussion The results of this focus group analysis demonstrate support for future Saleema campaign efforts promoting awareness and community engagement. The campaign could capitalize on partnerships with young people and those who are respected in the community (e.g., religious leaders) or continue promoting common values aligning with the support of education and community solidarity. Continuing campaign efforts have promise to decrease the harms of FGM in Sudan.